The Comparison of Clinical Epidemiology of Hospitalized Patients with COVID-19 during the Third and Fourth Waves of the Pandemic in Gorgan - Samira Eshghinia; Rahmat Allah Sharifi Far; Naghimeh Hajimoradloo; Ali Sinesepehr; Ahmad Sohrsbi; Mousa Imeri; Amir Reza Khodanazar Kalti; Erfan Rezaie Shirazi; Roghieh Golsha (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. COVID-19 has turned into a global public health crisis. This study intended to compare demographic characteristics, disease severity, treatment methods, and clinical outcomes in hospitalized patients with COVID-19 during the third and fourth waves of the pandemic in Golestan Province, Iran. Methods. In this cross-sectional study, the clinical epidemiology of all COVID-19 patients, who were hospitalized in two educational hospitals in Golestan Province for 30 days from the start of the third and fourth waves of the coronavirus pandemic in 2021-2022, was assessed. Their electronic medical records were used to collect their epidemiological, demographic, laboratory, and clinical information and treatment outcome. Results. In all, 930 electronic medical records of the hospitalized patients (351 in the third wave and 579 in the fourth wave) were studied. In the third and fourth waves, 29.06% and 13.13% of the patients had severe COVID-19, respectively (P = 0.001). The number of deaths in the third wave was larger compared to the fourth wave (P = 0.015). The mean duration of hospitalization was longer in the third wave than in the fourth wave (P = 0.001). The drugs administered most in these two waves were remdesivir, dexamethasone, and heparin, and the patients who received these drugs were compared in the third and fourth waves (P = 0.001). Conclusion. The reduced rate of mortality in the fourth wave was compared to the third wave. This reduction can be attributed to the change in the national strategy adopted in terms of hospitalization criteria and treatment protocols taking into account the acquired experience, earlier hospitalization, and start of drug therapy.